Case-study of teaching technological literacy for laboratory technological professions in the framework of computational thinking - Frank Jørgensen, Søren; Heiberg, Therese; Lorenzen, Henriette; Birk, Torben; E. Møller, Morten; Liikanen, Eeva; Bijwaard, Harmen; de Vries, Geert; Fjellaksel, Richard; Johansen, Kurt; Grünenberg, Kristina; Ellegaard, Marianne (Tidsskriftet Læring og Medier (LOM), 2025)
Technological literacy (TL) is a central theme in healthcare and laboratory professional education. The rapid speed of technological development in the healthcare sector, clinical and laboratory practice calls for new knowledge, skills and attitudes in future professionals and therefore for new approaches in teaching. Here we describe a teaching approach, based on computational thinking (CT) and aimed at increasing the TL of biomedical laboratory science (BLS) students. We discuss the background for why we use CT as framework, the intended learning outcomes and how these link to the needs in the students´ future practice. Furthermore, in an international network of teachers and researchers in the BLS, Chemical and Biotechnical Science and radiography education programs, we carried out a systematic observation study of parts of the teaching and used the reflection notes from the observer group to discuss how the intended TL competencies play out in the teaching sessions and the students´ activities in these. We discuss how the teaching approaches support, or not, the development of the students´ TL. This study is part of an Erasmus+ network aimed at developing novel teaching approaches to support students´ technological literacy.